Balanced scorecard-based evaluation of digitalization and technological transformation performance of small businesses - Dinçer, Hasan; Yüksel, Serhat (Academic Press, 2024)
Digitalization has become even more popular, especially in recent years, with the radical development of technology under sustainability. This situation has also affected businesses significantly. To survive in the increasingly competitive conditions at the end of globalization, businesses need to attach great importance to digitalization. This situation is of vital importance especially for small-scale enterprises. These businesses have to compete with large-scale international companies in order to maintain their profitability. Therefore, these businesses need to take appropriate steps towards digitalization. Otherwise, these companies will not be able to maintain their presence in the sectors for a long time. This study aimed at evaluating digitalization and technological transformation performance of small businesses. In this framework, the main research question is to understand which indicators play more critical role for the purpose of performance improvements of the small businesses with respect to the digitalization. For this purpose, a novel hybrid fuzzy decision-making model has been constructed. In the first stage of this model, critical indicators are weighted by using facial expression-based Quantum Spherical fuzzy DEMATEL technique. Within this scope, the perspectives of balanced scorecard approach are taken into consideration. On the other hand, in the second stage of the proposed mode, E7 countries are examined by considering facial expression-based Quantum Spherical fuzzy TOPSIS methodology. In this process, it can be possible to define which of these countries are more successful regarding the digitalization performance of the small businesses. With the help of the analysis results of this model, specific and effective investment strategies can be identified for the small businesses. These strategies can have a positive influence on the performance improvements of the small business so that they can survive in the competitive market in a more successful manner. Moreover, this situation has a powerful contribution to the sustainable development of the countries. It is concluded that revenue generated from digital channels (C1) is the most influencing factor because it affects all other three criteria. Innovation capacity (C4) is also found as the most critical indicator since it has the greatest weight (0.252). It is identified that Indonesia has the greatest performance regarding the digitalization and technological transformation. Similarly, India and China are other successful countries within this context. However, Brazil and Mexico have lower performance for this situation. Strengthening the innovation capacity is important to increase the success of digitalization and technological transformation. An innovative culture must be established within the organization to foster innovation.
Keywords: Business Administration; Computer in Society; Computer Science; Information Systems; Management; Operations Management; Technological Change; Technology Management